Synthesis of a Vanadium-Substituted Fe–Ti-Based Ternary Alloy via Mechanical Alloying, Compacting, and Post-Annealing - Abhishek Kumar Patel; Davide Violi; Ivan Lorenzon; Carlo Luetto; Paola Rizzi; Marcello Baricco (Metals)
In this study, we address the need for sustainable and scalable synthesis routes for hydrogen storage materials by developing a FeTi alloy in which vanadium (V) partially substitutes for titanium (Ti). The alloy was synthesized using mechanical alloying, compaction, and post-annealing, employing industrial-grade Fe and Ti powders and an alternative to pure vanadium, i.e., ferrovanadium (Fe–V). X-ray diffraction (XRD) analysis of the mechanically alloyed mixture revealed the partial formation of a Fe(V) solid solution, along with residual Ti. Subsequent compaction and annealing at 1000 °C led to the formation of the FeTi(V) phase, accompanied by two minor secondary phases, Fe2Ti and Fe2Ti4O. A maximum phase yield of 90% for FeTi was achieved after 48 h of annealing. The novelty of this work lies in the demonstration of a sustainable and economical synthesis approach for V-substituted FeTi alloys using industrial-grade raw materials, offering a potential reduction in the carbon footprint compared with conventional melting techniques.